Penerapan Model Pembelajaran Numbered Heads Together (NHT) Untuk Meningkatkan Prestasi Belajar Matematika Masa Covid-19 pada Siswa Kelas IX-B SMPN 3 Masbagik - Widyowati, Hernanik (MASALIQ, 2021)
This research is a classroom action research (CAR) aimed at improving mathematics learning achievement which is carried out in class IX-B students of SMPN 3 Masbagik using the Numbered Heads Together (NHT) Learning Model. The researcher conducted an action research with the aim of knowing the improvement of Mathematics achievement in class IX-B students of SMPN 3 Masbagik through the application of the Numbered Heads Together (NHT) learning model. Based on the results of research and discussion of the NHT learning model, it can increase the activity and learning achievement of mathematics students in class IX-B SMPN 3 Masbagik in the odd semester of the 2020/2021 school year. This increase can be seen from the acquisition of student activity scores and the average class value and the level of classical completeness in each cycle has increased both in cycle I and cycle II. Based on the results of data analysis in each cycle, it appears that the results from cycle I to cycle II have increased. In the implementation of learning and the results of the first cycle of data analysis, for student activities an average value of 2.74 was obtained and student activities in the second cycle obtained an average class value of 3.85 while classical completeness was obtained in the first cycle of 76% and increased in cycle II by 91%.